A meta-ethnography to synthesise household cultural research for climate change response. Issue 12 (1st December 2016) - Head, Lesley; Gibson, Chris; Gill, Nicholas; Carr, Chantel; Waitt, Gordon
ABSTRACT: Cultural change is critical to climate change responses, but the in-depth qualitative research that investigates culture is necessarily conducted at scales difficult to integrate with policy. A focus of climate change mitigation and adaptation is affluent developed world households. Adapting methods used elsewhere in social science, we report and assess a meta-ethnography of household sustainability research, scaling up findings from 12 studies encompassing 276 Australian households. Seven themes are dominant: family concerns are central to household practice; adaptiveness is contingent but more pervasive than often assumed; households make sense of climate change not through abstract arguments, but through physical resources and materials; boundaries of the home space are dynamic and subjective; daily time is an important currency; paradoxes abound among everyday practice; and privacy and a sense of autonomy are prioritised. Insights from the method include new light on familiar themes when seen through an environmental lens, thickening and triangulation of existing research, and a stronger basis for international comparisons. Some findings have straightforward application to policy, others identify potential areas of risk and resistance, others still are more conceptual. We conclude the method has considerable potential and is worth developing further, providing a critical perspective is maintained.